2018
DOI: 10.3390/nu10040389
|View full text |Cite
|
Sign up to set email alerts
|

Total and Added Sugar Intake: Assessment in Eight Latin American Countries

Abstract: Non-communicable diseases are growing at an alarming rate in Latin America. We assessed total and added sugar intake in Argentina, Brazil, Chile, Colombia, Costa Rica, Ecuador, Peru, and Venezuela, to verify the adequacy of the World Health Organization’s recommendations, considering gender, socioeconomic level (SEL) and age. A total of 9218 non-institutionalized individuals living in urban areas (age range 15–65 years) were assessed in the Latin American Study of Nutrition and Health (ELANS), a multicenter ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
70
1
11

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 43 publications
7
70
1
11
Order By: Relevance
“…In North America, this number increases to between 10 and 14% of the total calorie intake . Recently, the first data on dietary intake were published for eight countries in Latin America, showing that mean AS intake in these countries accounted for 13.2%TE consumption . In the present study, we confirmed that, in Argentina, the intake of AS exceeded the current recommendations, accounting for a mean of 15.9%TE intake, which is twice the amount consumed in countries such as Spain…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In North America, this number increases to between 10 and 14% of the total calorie intake . Recently, the first data on dietary intake were published for eight countries in Latin America, showing that mean AS intake in these countries accounted for 13.2%TE consumption . In the present study, we confirmed that, in Argentina, the intake of AS exceeded the current recommendations, accounting for a mean of 15.9%TE intake, which is twice the amount consumed in countries such as Spain…”
Section: Discussionsupporting
confidence: 86%
“…Unlike in Spain, where only adolescents reach 10% of total daily calories from AS, in Argentina, all age groups exceeded this cut‐off point. In Latin America, a similar trend towards a decrease in AS intake (and %TE) with increasing age was found, with a mean of 13.9%TE intake of AS in adolescents, against 12.1% in older adults . Data from the USA has shown a linear decrease in calorie intake from AS with age, both in men and women.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations